“Absenplus” Face Recognition and Geolocation Based on Android Application - Firmansyah; Eko Junirianto; Eny Maria (Politeknik Pertanian Negeri Samarinda, 2022)
The attendance system is an absolute requirement for attendance in various activities. In an agency or company, attendance becomes input for the administration department in assessing employee attendance. The manual attendance process is also less effective for employees or students where there is a possibility of fraud in carrying out attendance activities. The android “Absenplus” attendance application that implements face recognition and geo location methods that integrates with the web api which serves as an integration bridge between request and response data. With the application of face and location recognition methods, it can overcome the possibility of fraud in carrying out attendance. It is expected from this research that every attendance activity can be done easily and can view the attendance history of attendance from users of the “Absenplus” application. From the results of testing and implementation of face and location recognition methods into the “Absenplus” application system, it is declared valid. It can be seen from the test results that the correlation value of significance is greater than the value of r-table (0.532). It can be concluded that the “Absenplus” application can make it easier for users to carry out attendance activities.